ENVIRONMENTAL IMPACT OF WASTE IN DENTAL CARE: EDUCATIONAL STRATEGIES TO PROMOTE ENVIRONMENTAL SUSTAINABILITY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Dental practice generates significant waste with significant environmental impact, but the lack of awareness and education about sustainability in dental waste management postulates challenges for public health and professional training, so effective educational strategies are needed to promote sustainable practices and environmentally responsible dental care. The study used a mixed longitudinal approach to evaluate changes in dental students. Data were collected from 15 students through surveys, interviews as well as documentary analysis. Educational strategies were designed and implemented, followed by rigorous statistical and qualitative analysis, ensuring validity and research ethics. After the course, a significant increase in knowledge was observed, with more than 80% of the students acquiring basic knowledge about the types of pollutants and their environmental impact. In addition, there was a positive change in attitudes, with more than 70% expressing greater awareness and two willingness to adopt sustainable practices in disposal management. Students also recognized the importance of caring for the environment, with more than 80% showing a greater willingness to implement sustainable practices in their future professional practice. Environmental education is fundamental to the promotion of sustainable practices in dental care. Educational strategies can generate significant changes in students' knowledge, attitudes and perceptions, influencing the adoption of more sustainable practices in clinical practice.